In Vitro Inhibition of Cellulolytic Enzymes of Fusarium Oxysporum by Trichoderma spp and Pseudomonas Fluorescens on Arachis Hypogaea L - Rajeswari, P. (International Journal of Applied Sciences and Biotechnology, 2015)
In an attempt to develop biocontrol system for management of Fusarium wilt in groundnut, Trichoderma viride, Trichoderma harzianum,and Pseudomonas fluorescens were evaluated for their antagonistic activity against Fusarium oxysporum in vitro. .Fusarium wilt diseasescaused by the fungus Fusarium oxysporum lead to significant yield losses of crops. Experiments were conducted on the effect of culture filtratesof T.viride (1%), T. harzianum (1.5%), and P. fluorescens (2%) on the in vitro inhibition of cellulolytic enzymes of Fusarium oxysporum. Theactivity of 1,4 endoglucanases, 1,4exoglucanase Cellobiase produced by Fusariumoxysporum was higher, when compared to control.Maximum inhibition of above Cellulolytic enzymes (1, 4 endoglucanases, 1,4exoglucanase, Cellobiase) was shown by T. viride treatment wasfollowed by T. harzianum and P. fluorescens. Of all the treatments, T. viride treatment showed higher rate of inhibition of Cellulolytic enzymesof Fusarium oxysporum followed by that of T. harzianum and P. fluorescens.This present study indicates that culture filtrate of T.viride(1%)is the best biocontrol agent in the inhibition of Fusarium oxysporum causing Fusarium wilt of Arachis hypogaea .L DOI: http://dx.doi.org/10.3126/ijasbt.v3i1.12138 Int J Appl Sci Biotechnol, Vol. 3(1): 106-110